Incorporação de óxido de zinco ou extrato de própolis em um cimento de ionômero de vidro modificado por resina : efeito nas propriedades mecânicas e citotoxicidade - Scheid, Patrícia Alves (2014)
Resin-modified glass-ionomer cement (RMGIC) is mainly indicated as a liner or base in restorative materials. In deep dentinal cavities where there is not symptomatology, only partial dentine is removed in order to avoid the pulp exposure. Thus, the restorative material is very close to the pulp. The aim of this study was to evaluate the incorporation of zinc oxide or extract of propolis in a RMGIC, subsequently testing the mechanical properties and citotoxicity. For the control group, the RMGIC (Vitremer, 3M ESPE) was handled in its original formulation (G7). Zinc oxide was inserted to the powder of RMGIC in the following proportions: 10% (G1), 20% (G2) e 30% (G3), which were mixed with the original liquid of Vitremer. The extract of propolis was inserted to the liquid of Vitremer in the following proportions: 10% (G4), 20% (G5), 30% (G6), which were mixed with the original powder of Vitremer. Compressive strength, diametral tensile, microhardness and roughness were measured. The cytotoxity was evaluated by MTT assay and neutral red after 24 and 48 hours of exposition. Data were analyzed using the IBM SPSS 22. To verify normality and homogeneity, Shapiro-Wilk and Levene tests were used, respectively, with significance level of 5%. The roughness, microhardness and compressive strength were assessed by one-way ANOVA followed by a multiple-comparison Tukey post hoc test. The diametral tensile was assessed by one-way ANOVA followed by a multiple-comparison Games-Howell post hoc test. For cytotoxity tests, one-way ANOVA and Duncan post hoc test was used to identify intergroup differences. The level of significance was set at p < 0,05. No significant difference was observed in the compressive strength and diametral tensile amog groups in relation to control group (G7). Groups 2, 4 e 6 did not differ in microhardness to the control group (G7). In the roughness test, the group 6 presented the highest mean statistical difference from group 7. Experimental groups showed similar or highest values of cell viability when compared to the group 7 in MTT assay and neutral red tests. The addition of 10% and 20% of extract of propolis or zinc oxide do not interfere in the mechanical proprieties and cytotoxicity of RMGIC.